COVID-19, Diabetes, and Associated Health Outcomes in China: Results from a Nationwide Survey of 10 545 Adults - Shi, Zumin; Yan, Alice; Zimmet, Paul; Sun, Xiaoming; Cristina do Vale Moreira, Nayla; Cheskin, Lawrence J.; Wang, Liming; Qu, Weidong; Yan, Hong; Hussain, Akhtar; Wang, Youfa (Hormone and Metabolic Research, 2021)
This study examined the associations between diabetes and self-reported/familial COVID-19 infection and investigated health-related outcomes among those with diabetes during China’s nationwide quarantine. The 2020 China COVID-19 Survey was administered anonymously via social media (WeChat). It was completed by 10 545 adults in all of mainland China’s 31 provinces. The survey consisted of 74 items covering sociodemographic characteristics, preventive measures for COVID-19, lifestyle behaviors, and health-related outcomes during the period of quarantine. Regression models examined associations among study variables. Diabetes was associated with a six-fold increased risk of reporting COVID-19 infection among respondents or their family members. Among people with diabetes, individuals who rarely wore masks had double the risk of suspected COVID-19 infection compared with those who always wore masks, with an inverse J-shaped relationship between face mask wearing and suspected COVID-19 infection. People with diabetes tended to have both poor knowledge of COVID-19 and poor compliance with preventive measures, despite perceiving a high risk of personal infection (40.0% among respondents reporting diabetes and 8.0% without diabetes). Only 54–55% of these respondents claimed to consistently practice preventive measures, including wearing face masks. Almost 60% of those with diabetes experienced food or medication shortages during the quarantine period, which was much higher than those without diabetes. Importantly, respondents who experienced medication shortages reported a 63% higher COVID-19 infection rate. Diabetes was associated with an increased risk of self-reported personal and family member COVID-19 infection, which is mitigated by consistent use of face masks.
Keywords: COVID-19; pandemic diabetes; non-communicable diseases; health outcomes; China